Sugammadex Improves Neuromuscular Function in Patients Receiving Perioperative Steroids - Ozer, A. B.; Bolat, E.; Erhan, O. L.; Kilinc, M.; Demirel, I.; Toprak, G. Caglar (Medknow Publications & Media Pvt Ltd, 2018)
Context: Sugammadex has steroid-encapsulating effect. Aim: This study was undertaken to assess whether the clinical efficacy of sugammadex was altered by the administration of steroids. Setting and Design: Sixty patients between 18 and 60 years of age with the American Society of Anesthesiologists IuIV and undergoing elective direct laryngoscopy/biopsy were included in this study. Materials and Methods: Patients were assigned to two groups based on the intraoperative steroid use: those who received steroid (Group S) and who did not (Group C). After standard general anesthesia, patients were monitored with the train of four (TOF) monitoring. The preferred steroid and its dose, timing of steroid administration, and TOF value before and after sugammadex as well as the time to recovery (TOF of 0.9) were recorded. Statistical Analysis Used: SPSS software version 17.0 was used for statistical analysis. Results: There is no statistically significant difference between groups in terms of age, gender, preoperative medication use, and TOF ratio just before administering sugammadex. The reached time to TOF 0.9 after sugammadex administration was significantly shorter in Group S than Group C (P < 0.05). A within-group comparison in Group S showed no difference in TOF ratio immediately before sugammadex as well as the dose of sugammadex in those who received prednisolone; time to TOF 0.9 was higher in prednisolone receivers as compared to dexamethasone receivers (P < 0.05). Conclusion: In patients receiving steroids, and particularly dexamethasone, an earlier reversal of neuromuscular block by sugammadex was found, in contrast with what one expect. Further studies are required to determine the cause of this effect which is probably due to a potential interaction between sugammadex and steroids.
Keywords: Anesthesia; steroids; sugammadex; train-of-four monitoring